2005
DOI: 10.1093/jjco/hyi192
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ramosetron and Granisetron for the Prevention of Acute and Delayed Emesis in Cisplatin-Based Chemotherapy: a Randomized Controlled Trial

Abstract: Ramosetron is effective and safe for the control of acute and delayed emesis induced by cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 2 publications
3
11
0
Order By: Relevance
“…Similar findings have been observed in other trials as well. 11,14 In the present study, the ramosetron group showed a better impact on the quality of life than palonosetron and granisetron in both the acute and delayed phases which can be correlated with better complete response rates in the acute and delayed phases and better control of nausea than palonosetron and granisetron. The mean FLIE questionnaire scores in the acute and delayed phases were better in ramosetron group and a higher proportion of patients showed no impact on daily living (NIDL) as defined by a FLIE score of >108 in both the acute and delayed phases.…”
Section: Figure 3 Comparative Effect Of the Study Drugs In Controllisupporting
confidence: 53%
See 2 more Smart Citations
“…Similar findings have been observed in other trials as well. 11,14 In the present study, the ramosetron group showed a better impact on the quality of life than palonosetron and granisetron in both the acute and delayed phases which can be correlated with better complete response rates in the acute and delayed phases and better control of nausea than palonosetron and granisetron. The mean FLIE questionnaire scores in the acute and delayed phases were better in ramosetron group and a higher proportion of patients showed no impact on daily living (NIDL) as defined by a FLIE score of >108 in both the acute and delayed phases.…”
Section: Figure 3 Comparative Effect Of the Study Drugs In Controllisupporting
confidence: 53%
“…Previous studies comparing ramosetron and granisetron for prevention of acute and delayed emesis have revealed similar efficacies and concluded that the two drugs may be used interchangeably for preventing CINV. 11,14 In a study of palonosetron compared with granisetron for the prevention of chemotherapy-induced nausea and vomiting in Chinese population, palonosetron consistently produced numerically higher complete response rates than granisetron in the acute phase and delayed phase, though the differences were not significant. 15 In a comparative study of antiemetics for the prevention of postoperative nausea and vomiting after laparoscopic gynaecologic surgery, the number of complete responders at 48 h after the surgery was maximum for ramosetron, though the differences between the groups were not statistically significant.…”
Section: Figure 3 Comparative Effect Of the Study Drugs In Controllimentioning
confidence: 99%
See 1 more Smart Citation
“…Ramosetron administered alone was as effective as granisetron or ondansetron for CINV prevention in clinical trials [10][11][12]. In combination with dexamethasone, ramosetron showed a 77% CR rate in acute period, which is comparable to that of granisetron (82%) [16].…”
Section: Discussionmentioning
confidence: 89%
“…10 Ramosetron has been introduced for the treatment of irritable bowel syndrome (IBS), chemotherapy (cisplatin)-induced nausea and vomiting and late in post-operative nausea and vomiting, with almost no study done for comparing the level of satisfaction of patients receiving this drug with other antiemetics. [11][12][13] Patient satisfaction is very important in modern health care system. Though, it is difficult to assess as no golden standard is available, still one of the methods is by using visual analogue scale (VAS) scoring.…”
Section: Introductionmentioning
confidence: 99%